Research in the social scientific study of religion. - Piedmont, Ralph L., 1958-; Village, Andrew (Research in the Social Scientific Study of Religion, 2013)
The twenty-fourth volume of RSSSR includes a landmark collection of papers on religion, spirituality, and health, as well as papers on other key areas in the study of religion such as spirituality and faith development.